Simulated moderate hypoxia reduces intermittent sprint performance in games players - Turner, G.; Gibson, O. R.; Maxwell, N. S. (The Journal of Sports Medicine and Physical Fitness, 2014)
BACKGROUND: Exercise at altitude places additional physiological stress on the individual in comparison with sea-level performance. This study examines the effect of a moderate hypoxic environment (FiO2=~17%) on intermittent sprint exercise performance.